The Quality Gravity Model with an Application to Chinese Imported Fruits - Xu Tian; Xiaohua Yu (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
Derived from unit value and the gravity model, this paper proposes a simple model to analyze the quality determinants of imported fruits in China, and finds that (1) both quantity and price are exogenous for quality, and quality decreases in quantity but increases in price; (2) the own-income elasticity of quality is 8.55 and the partner-income elasticity is only -0.08; and (3) distance and common boundary do not play significant roles in determining quality.
Keywords: 330; Gravity model; Quality index; Quality Gravity model